1984
DOI: 10.1159/000132046
|View full text |Cite
|
Sign up to set email alerts
|

A 39,X/40,XY/41,XYY mosaic male mouse

Abstract: Cytogenetic analyses of bone marrow and gonadal cells in a male mouse, which appeared to be normal, revealed mosaicism in both tissues. Three chromosome complements, 39, X, 40, XY, and 41, XYY, were found in both bone marrow and spermatogonia, while only the last two complements were found in spermatocytes. In this mouse, unlike in the human, the XYY cells showed a proliferative advantage over the XY cells. In XYY cells at diakinesis/metaphase I the gonosomes showed all possible types of association, and a pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…XYY MI spermatocytes have been common. In the mosaics described by Das and Behera (1984) and Searle and Wilkinson (1986), there was no preferential loss of XYY cells prior to MI. whereas in the present mosaics a dramatic reduction in the fre quency of XYY cells occurred during pachytene.…”
Section: Discussionmentioning
confidence: 87%
“…XYY MI spermatocytes have been common. In the mosaics described by Das and Behera (1984) and Searle and Wilkinson (1986), there was no preferential loss of XYY cells prior to MI. whereas in the present mosaics a dramatic reduction in the fre quency of XYY cells occurred during pachytene.…”
Section: Discussionmentioning
confidence: 87%
“…The relative frequencies of the various sex chromosome associations at diakinesis and the first meiotic metaphase (MI) are very heterogeneous and have been taken to suggest either random synapsis of the three sex chromosomes (resulting in twice as many XY bivalent/Y univalent as X univalent/YY bivalent associations) or a synaptic advantage of the X over either Y chromosome (Cattanach and Pollard, 1969;Evans et al, 1969Evans et al, , 1978Rathenberg and Müller, 1973;Manna and Roy, 1980;Das and Kar, 1981;Das and Behera, 1984). However, as is evident from the study of Rodriguez and Burgoyne (2000), the frequencies of the various sex chromosome associations at diakinesis/MI bear little resemblance to those at pachytene, when synapsis is first completed.…”
mentioning
confidence: 99%
“…Of these cells, 19 had an XYY trivalent, 18 had an X univalent and YY bivalent, 1 had an XY bivalent and Y univalent, and 1 had X, Y, Y univalents. There is an intriguing contrast between these observations which indicated preferential involvement of the Y chromosomes in synapsis and the metaphase I data which suggested either random X and Y association (Rathenberg & Muller, 1973;Das & Kar, 1981) or preferential X chromosome involvement (Evans et al 1978;Das & Behera, 1984). This brief report describes the synaptic behaviour of the sex chromosomes in pachytene spermatocytes of another XYY male.…”
Section: Introductionmentioning
confidence: 87%
“…In contrast, Evans et al (1978) concluded the X chromosome had an overall pairing advantage as it was present as a univalent on fewer occasions than expected of random association. Das & Behera's (1984) data also indicated a paucity of X chromosome univalence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation